2016
DOI: 10.3233/jad-160175
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Neural Bases of Cognitive and Affective Empathy Deficits in Alzheimer’s Disease and the Behavioral-Variant of Frontotemporal Dementia

Abstract: Loss of empathy is a core presenting feature of the behavioral-variant of frontotemporal dementia (bvFTD), resulting in socioemotional difficulties and behavioral transgressions. In contrast, interpersonal functioning remains relatively intact in Alzheimer's disease (AD), despite marked cognitive decline. The neural substrates mediating these patterns of loss and sparing in social functioning remain unclear, yet are relevant for our understanding of the social brain. We investigated cognitive versus affective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
121
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 79 publications
15
121
2
Order By: Relevance
“…Rankin and colleagues (Rankin et al, 2006) performed a brain-behavior correlation analysis across NDG patients with a diverse range of atrophy patterns and found that empathy strongly corresponded to volume in predominantly right anteromedial temporal and inferior frontal structures. Reviews of the broader empathy and lesion literature further support the relationship between right frontotemporal regions and empathy, with ventromedial PFC, inferior frontal gyrus (IFG), orbitofrontal cortex (OFC), superior temporal gyrus (STG), right temporal pole, anterior insula, amygdala, and caudate appearing across multiple lesion studies (Hillis, 2014; Olson et al, 2007) However, in contrast, Dermody and colleagues found primarily left inferior frontoinsular correlates in NDG patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) (Dermody et al, 2016). Fewer structural correlation studies have been attempted in healthy samples, likely due to methodological issues arising from lack of variance in brain volume, but one such study also found primarily left subcortical structures to correlate with empathy (Banissy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rankin and colleagues (Rankin et al, 2006) performed a brain-behavior correlation analysis across NDG patients with a diverse range of atrophy patterns and found that empathy strongly corresponded to volume in predominantly right anteromedial temporal and inferior frontal structures. Reviews of the broader empathy and lesion literature further support the relationship between right frontotemporal regions and empathy, with ventromedial PFC, inferior frontal gyrus (IFG), orbitofrontal cortex (OFC), superior temporal gyrus (STG), right temporal pole, anterior insula, amygdala, and caudate appearing across multiple lesion studies (Hillis, 2014; Olson et al, 2007) However, in contrast, Dermody and colleagues found primarily left inferior frontoinsular correlates in NDG patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) (Dermody et al, 2016). Fewer structural correlation studies have been attempted in healthy samples, likely due to methodological issues arising from lack of variance in brain volume, but one such study also found primarily left subcortical structures to correlate with empathy (Banissy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly however, our findings from the perceptual encoding condition do not support this position, as we did not find enhanced source memory retrieval for both the self- and other-reference conditions compared to the perceptual condition. Furthermore, while perspective taking and ToM deficits have been widely reported in bvFTD patients (Adenzato, Cavallo, & Enrici, 2010; Bertoux, Funkiewiez, O’Callaghan, Dubois, & Hornberger, 2013; Kipps & Hodges, 2006), recent work has delineated between cognitive (attribution of intention) and affective (attribution of emotion) ToM, showing comparable deficits in cognitive ToM across both bvFTD and AD patients (Dermody et al, 2016; Dodich et al, 2016). Against this background, the anterior-dorsal CMS involvement in SRE magnitude across both bvFTD and AD patients may be related to deficits in their ability to evaluate information from the perspective of another person.…”
Section: Discussionmentioning
confidence: 98%
“…The finding that dorsal MPFC supports judgements about others is unsurprising, given its role in perspective taking tasks, such as those involving theory of mind (ToM) (D’Argembeau et al, 2007; Gallagher & Frith, 2003). Crucially, bvFTD patients show impairments in perspective taking and empathy (Cerami et al, 2014; Dermody et al, 2016; Eslinger et al, 2011), which have been proposed to be associated with underlying difficulties in inhibiting their own perspective when required to adopt another person’s perspective (Le Bouc et al, 2012). It is therefore possible that bvFTD patients tended to encode all stimuli in relation to the self, thereby reducing the SRE magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…7) of the present study was found between the left orbitofrontal cortex and the left anterior inferior and middle temporal gyri. The literature suggests a functional role of this connection in deficient socioemotional abilities that are found predominantly in the behavioral variant of FTD [74] , and in higher level object representation, involving language and auditory processing. Unlike in connection no.…”
Section: Discussionmentioning
confidence: 99%